Gender Differences in Suicide and Spouse killing in the Qajar Era - Mohammad Hosein Sharifi Saei (پژوهشنامه مددکاری اجتماعی, 2021)
The aim of this study was to identify the causes of suicide and homicide in the Qajar period. This study has been done by content analysis method (quantitative and qualitative). The text under analysis was "police reports on the situation in Tehran during the reign of Nasser al-Din Shah Qajar." The findings of this study showed that suicide in the Qajar era is a pervasive phenomenon. In all cases (except one), the means of suicide among men and women was "opium eating." In the Qajar era, women "attempted suicide" more than men, but the rate of "suicides leading to death" was higher in men than women. On the other hand, "economic poverty" was the most important cause of men's suicide. Nearly half of all male suicides were due to economic poverty, but the most important cause of female suicide was the experience of "domestic violence." No woman has committed suicide due to economic problems. Most women commit suicide in their husbands' homes after a conflict with their husbands. According to police reports, no man had attempted to kill his wife, but in several cases, women attempted to kill their husbands. Women usually committed suicide after repeated experiences of domestic violence, but sometimes tried to kill their husbands in revenge.